2010
DOI: 10.1093/ndt/gfq442
|View full text |Cite
|
Sign up to set email alerts
|

Troponin I levels in asymptomatic patients on haemodialysis using a high-sensitivity assay

Abstract: Using a new-generation, high-sensitivity assay, over a third of asymptomatic ESRD patients have an elevated TnI. The significance of these low-level elevations is unclear at this time. TnI levels remain stable over a 3-month period in most patients. HD treatment does not appear to affect the TnI level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 12 publications
8
58
3
Order By: Relevance
“…Hs-cTnT levels are strongly associated with left ventricular hypertrophy in a large dialysis cohort [16], and a predictor of death in several recent reports [17,18,19]. However, the utility of a combination of hs-cTnT with natriuretic peptides for recognizing patients at high risk for major CV events or death has still not been explore.…”
Section: Introductionmentioning
confidence: 99%
“…Hs-cTnT levels are strongly associated with left ventricular hypertrophy in a large dialysis cohort [16], and a predictor of death in several recent reports [17,18,19]. However, the utility of a combination of hs-cTnT with natriuretic peptides for recognizing patients at high risk for major CV events or death has still not been explore.…”
Section: Introductionmentioning
confidence: 99%
“…We found, that by using a more sensitive cTnT assay 94% of our patients had cTnT elevations above the 99 th percentile with the hs-cTnT assay (Jacobs et al, 2009). Others have similarly found a larger amount of cTnI elevations in ESRD patients by using more sensitive cTnI assays (Hickman et al, 2007;Kumar et al, 2010). With respect to the occurrence of cTn elevations in ESRD patients one should also take into account that the cTn concentrations in ESRD patients can vary over time, even in otherwise clinically stable patients.…”
Section: Fig 3 (A)mentioning
confidence: 60%
“…The exact frequency of these elevations varies somewhat between studies, depending on the patient inclusion criteria, the applied cut-off values and the troponin assay used. In general, cTnT has been found elevated more often than cTnI (roughly 53% for cTnT and 17% for cTnI as reviewed in (Kanderian & Francis, 2006)) although recent publications, using more sensitive assays suggest that the frequency of cTnT and cTnI elevations are similar (Hickman et al, 2007;Kumar, Michelis, Devita, Panagopoulos, & Rosenstock, 2010). It is important to note that the number of detected cTn elevations depends on the cut-offs that are used to define elevated values.…”
Section: Cardiac Troponin Elevations In Esrdmentioning
confidence: 99%
“…Our current study shows that even moderate elevations of cTnI, even below or slightly higher than the 99th percentile in 59.2% of patients in this study. In the study by Kumar et al [ 11 ], 75% of patients had stable cTnI values over time. Our study demonstrates that the mean cTnI of 3-monthly measurements show a similar correlation with mortality compared to a random (first) measurement.…”
Section: Discussionmentioning
confidence: 92%
“…Diverse outcomes in previous studies addressing the association of cTnI with mortality were in part due to problems with the standardization of cTnI assays. One high-sensitivity cTnI assay has recently been studied in hemodialysis patients by Kumar et al [ 11 ], but this study had a smaller group of patients with a shorter follow-up and mortality was not reported. Our current study shows that even moderate elevations of cTnI, even below or slightly higher than the 99th percentile in 59.2% of patients in this study.…”
Section: Discussionmentioning
confidence: 99%